1996
DOI: 10.1046/j.1471-4159.1996.67052051.x
|View full text |Cite
|
Sign up to set email alerts
|

Inosine Mediates the Protective Effect of Adenosine in Rat Astrocyte Cultures Subjected to Combined Glucose‐Oxygen Deprivation

Abstract: Preliminary evidence suggests adenosine, a neuromodulator, has neuroprotective properties during cerebral ischemia. It is unclear, however, if adenosine has glioprotective effects. We studied the effect of adenosine on cellular injury in astroglial cultures subjected to combined glucose-oxygen deprivation. Adenosine (100-1,000~tM)dramatically reduced astroglial injury, whereas the adenosine agonists 2-chloroadenosine (10 nM-100 bIM), N 6-cyclopentyladenosine (1 nM-10~.tM),5'-Nethylcarboxamidoadenosine (10 nM-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 40 publications
7
42
0
3
Order By: Relevance
“…19,20 Inosine is also capable of protecting astrocytes and neurons against hypoxia, ischemia and zinc sulfate in vitro. 15,18,29 The present study demonstrated that inosine could reduce apoptosis after crushing injury of the spinal cord. Secondary degeneration has been attributed to a number of mechanisms underlying cell death, including ATPdepletion, free radical overproduction, oxidative damage, cytokines and inflammation.…”
Section: Discussionsupporting
confidence: 59%
“…19,20 Inosine is also capable of protecting astrocytes and neurons against hypoxia, ischemia and zinc sulfate in vitro. 15,18,29 The present study demonstrated that inosine could reduce apoptosis after crushing injury of the spinal cord. Secondary degeneration has been attributed to a number of mechanisms underlying cell death, including ATPdepletion, free radical overproduction, oxidative damage, cytokines and inflammation.…”
Section: Discussionsupporting
confidence: 59%
“…23 The neuroprotective effects of inosine during OGD have been reported in cultured cells, although the culture systems do not perfectly simulate the real brain during ischemia. 22,24 On the other hand, ADA itself may also modify the adenosine receptors directly. A 1 , A 2A , and A 2B receptors are ADA-anchoring membrane proteins and the anchored ADA could alter the properties of the adenosine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…16 Since ADA-deficient patients suffer from noninfectious respiratory distress and severe hypoxia, 18,19 it is possible that they have a higher risk of cerebral hypoxia, which could result in brain lesions including the basal ganglia. Assuming that this increased risk of hypoxia is seen in ADA deficiency, there are four candidates to explain the abnormalities in the central nervous system (CNS): (1) the increased adenosine levels impair the CNS via A 2A receptors, 20,21 (2) the increased deoxy-adenosine levels are toxic, 13 (3) the decreased inosine levels impair the CNS neuron survivability, [22][23][24] or (4) ADA affects adenosine receptors directly. 2 Since adenosine A 1 receptor agonists decrease brain damage induced by ischemic stress, 8 adenosine is a known neuroprotective agent.…”
Section: Introductionmentioning
confidence: 99%
“…Postoji nekoliko radova koji sugerišu da Ino doprinosi neuroprotekciji utičući na bolje preživljavanje astrocita u kulturi nakon deprivacije glukoze i kiseonika [111], kao i da Ino promoviše izrastanje aksona nakon povrede kod pacova [112]. Pored toga, smatra se da je Ino potencijalni kandidat u terapiji multiple skleroze [113], Turetovog sindroma [114] i moždane ishemije.…”
Section: Metabolizam Adenozinaunclassified
“…HX se dalje može metabolisati dalje ksantin-oksidazom do ksantina (X) ili, alternativno, može biti konvertovan do IMP posredstvom hipoksantin-guanin fosforibozil transferaze (HPGRT). Zabeleženo je da su tokom moždane ishemije nivoi HX povećani, ali je pokazano i da HX nema neuroprotekivna svojstva [111]. Sasvim suprotno, pokazano je da akumulacija HX doprinosi oksidativnom stresu nakon reoksigenacije tkiva; visoki nivoi HX su verovatno posledica povećanog utroška energije koja rezultira visokim nivoom metabolizma purina [115].…”
Section: Metabolizam Adenozinaunclassified